Diverse approaches to learning with immersive virtual reality identified from a systematic review - Won, Mihye; Ungu, Dewi; Matovu, Henry; Treagust, David F; Tsai, Chin-Chung; Park, Jungho; Mocerino, Mauro; Tasker, Roy (Elsevier, 2022)
To investigate how learning in immersive Virtual Reality was designed in contemporary educational studies, this systematic literature review identified nine design features and analysed 219 empirical studies on the designs of learning activities with immersive Virtual Reality. Overall, the technological features for physical presence were more readily implemented and investigated than pedagogical features for learning engagement. Further analysis with k-means clustering revealed five approaches with varying levels of interactivity and openness in learning tasks, from watching virtual worlds passively to responding to personalised prompts. Such differences in the design appeared to stem from different practical and educational priorities, such as accessibility, interactivity, and engagement. This review highlights the diversity in the learning task designs in immersive Virtual Reality and illustrates how researchers are navigating practical and educational concerns. We recommend future empirical studies recognise the different approaches and priorities when designing and evaluating learning with immersive Virtual Reality. We also recommend that future systematic reviews investigate immersive Virtual Reality-based learning not only by learning topics or learner demographics, but also by task designs and learning experiences.